Probing potential active sites and bipolar electric-field effects: Novel insights into the Li+ extraction mechanism on MoS2 in aqueous capacitive deionization - Xueli Zhang; Linhui Jia; Bing Chang; Dezhi Fang; Chengxing Cui; Silu Huo; Shuaiqi Ding; Yu Chen; Yang Li; Zhiyuan Chen; Runqiang Liu; Kexun Li (Desalination, 2026)

The dispersal and adaptation of Homo sapiens onto the Tibetan Plateau during MIS 3: an Initial Upper Paleolithic assemblage from Nwya Devu? - Peiqi Zhang; Xiaoling Zhang; Linhui Li; Wei He; Yingshuai Jin; Junyi Ge; Shejiang Wang; Nicolas Zwyns; Xing Gao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Effects of plant hedges and slope terraces on soil degradation on sloping farmland in the Chinese black soil region - Linhui Zhou; Libo Ye; Jialong Wu; Yu Zhang; Haiou Shen; Hongli Li (Ecological Engineering, 2026)

Enzymatic synthesis and characterization of human milk-simulated medium- and long-chain triglycerides: Bridging the MLCTs compositional gap for infant formula - Linhui Zeng; Shilu Deng; Jingzhi Wu; Liufeng Zheng; Jing Li; Zeyuan Deng (Food Bioscience, 2026)

Urban features dominate hot spots of extreme heat and elevate heat-related morbidity in 2024 over Yangtze River Delta - Siyang He; Jiacan Yuan; Chen Liang; Yuanhao Chen; Xiangyu Ao; Linhui Li; Alexander Baklanov; Renhe Zhang (Urban Climate, 2026)

Dihydroergotamine alleviates circadian rhythm disorders through predicted interaction with to CRY1 - Linhui Cai; Yixin Sun; Shuai Wang; Qianqian You; Wenlong Xie; Jian Zhang; Boan Li (Molecular Diversity, 2026)

Multi-thiol grafted PVA/PEI electrospun nanofibers via thiol-ene click chemistry for efficient and selective Au(III) recovery: Experimental and DFT insights - Hongxing He; Ying Xu; Xintao Yang; Peng Li; Enrui Dai; Yi Zhang; Min Li; Linhui Su; Yanjie Zhao; Zhifeng Nie (Desalination, 2026)

Species-specific salinity adaptation mechanisms drive niche partitioning of nitrite-dependent anaerobic methane oxidation bacteria in a natural wetland gradient - Zixuan Ren; Yuting Wen; Yushan Ma; Minghui Li; Lixin Wang; Ruihong Yu; Linhui Wu (Water Research, 2026)

SOC1 clade genes coordinate lateral root development and response to multiple phytohormonal and environmental stress signals in Arabidopsis - Xinyue Li; Qian Ma; Ping Jin; Yaxuan Wang; Tongyao Yang; Ying Chen; Shujuan Guo; Zisheng Zhang; Chengbin Xiang; Qiuling Wang; Linhui Yu (Journal of Plant Physiology, 2026)

Hierarchical hotspot engineering for ultrasensitive antibiotics sensing in human body fluids - Jiawen Li; Zhenghe Wang; Linhui Qian; Jianqiao Zhao; Zhengjun Zhang; Weipeng Wang (Chemical Engineering Journal, 2026)

Cerium-modified Cu-SSZ-13 catalysts: Enhanced low-temperature activity and hydrothermal stability for efficient NOx reduction - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Journal of Environmental Chemical Engineering, 2026)

Research on emission control performance of SSCR system based on multi-condition operation and three-high tests - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

The role of ammonia in the global energy transition: opportunities and challenges in ammonia gas turbine technology - Shuai Chen; Bin Guan; Lei Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

High-efficiency catalytic removal of N2O from ammonia-fueled engine exhaust - Bin Guan; Zhongqi Zhuang; Lei Zhu; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; Tiankui Zhu; et al. (Fuel, 2026)

Substituted diphenylamine antioxidants and synthetic phenolic antioxidants in leachate from domestic landfills in China: Occurrence and removal via treatment - Linhui Zhang; Fei Chen; Xianming Zhang; Xue Zhang; Bin Liang; Shanshan Bai; Zifeng Zhang; Yifan Li; Nanqi Ren (Journal of Hazardous Materials, 2025)

Human milk fat Substitutes alleviate dextran sulfate sodium induced cognitive deficits in mice by modulating brain fatty acid and ether Lipid metabolism - Yangzheng He; Linhui Zeng; Han Liao; Jing Li; Yong Sun; Hongyan Li; Ting Luo; Zeyuan Deng (Food Bioscience, 2025)

Hydrodynamic coefficient of tuna longline hook, bait and baited hook based on flume tank test - Bo Zhang; Liming Song; Yuwei Li; Yukun Qi; Linhui Wang; Meng Zhang; Hailin Hao (Fisheries Science, 2025)

Chrysin Attenuates Myocardial Cell Apoptosis in Mice - Gang Deng; Yongzheng Yang; Ouyang Qing; Jiang Linhui; Su Haotao; Chi Liu; Ge Li; Moussa Ide Nasser (Cardiovascular Toxicology, 2025)

Microbial community responses and functional shifts in carbon degradation driven by water-salt gradients in lakeshore wetlands of semi-arid lakes - Jialin Zhao; Xin Kou; Huamin Liu; Tiezheng Wu; Junyi Li; Yongman Wang; Hongliang Xie; Mingqi Wang; Linhui Wu; Lu Wen; Lixin Wang (Journal of Environmental Management, 2025)

Engineered albumin host for ratiometric fluorescent indicator-displacement assay: Distinguishing testosterone from estrone and estradiol - Yuting Luo; Linhui Peng; Zhang Lin; Zhiqing Xun; Na Li; Naiyu Liu; Yalong Wang; Xinfeng Du; Tianyi Qin; Bin Liu; Mingqiang Zhu (Chemical Engineering Journal, 2025)

Photothermal-driven micromotor for enhanced lithium extraction from salt-lake brines - Shihao Ding; Wenqian Xing; Ling Chen; Linhui Fu; Xinle Zhang; Zhen Luo; Qianqian Li; Mengting Qin; Jiang Gong; Jinping Qu; Ran Niu (Chemical Engineering Journal, 2025)

The natural stable isotope index for de novo structural elucidation of phytomolecules with geographical and biological tracing - Xiaojing Yan; Xin Zhou; Mingyang Gong; Weidan Li; Mingyue Zhang; Tianci Huo; Xinyu Jiang; Xiaoyuan Hu; Xingchen Huang; Linhui Liu; Xue Feng; Qisong Zhang; et al. (Analytica Chimica Acta, 2025)

Interpretable fish abundance index prediction in tuna longline fisheries: A LightGBM-SHAP case study in the tropical Atlantic Ocean - Linhui Wang; Liming Song; Hengshou Sui; Bin Li (Fisheries Research, 2025)

Soil moisture and abundance of microbial groups are key determinants of greenhouse gas fluxes in a semi-arid wetland ecosystem - Jiahui Yin; Junyi Li; Yongman Wang; Jialin Zhao; Zixuan Ren; Jia Li; Lixin Wang; Linhui Wu (Journal of Environmental Management, 2025)

Single-Cell RNA Sequencing Delineates the Atlas and Cell Interactions of the Testicular Cells in Chinese Soft-Shelled Turtle (Pelodiscus sinensis) - Jingting Yao; Sendong Li; Wenzhuo Ban; Linhui Zeng; Han Cui; Kaili Chen; Hongyan Xu (Marine Biotechnology, 2025)

Isolation and characterization of Polaribacter sargassicola sp. nov. and Algibacter ulvanivorans sp. nov.: two novel species with ability to degrade algal polysaccharides - Jin Li; Aihua Mao; Chao Peng; Linhui Li; Binghan Li; Lijuan Zhou; Yan Xu; Mingqi Zhong; Zhong Hu (Antonie van Leeuwenhoek, 2025)

Integrative proteogenomic and pharmacological landscape of acute myeloid leukaemia - Hanlin Wang; Jun-Yu Xu; Tao Wang; Gaoya Xu; Guanghao Luo; Mingya Zhang; Gusheng Tang; Chang Wang; Libing Wang; Weijia Fu; Xiong Ni; Linhui Zhai; et al. (Science Bulletin, 2025)

Hybrid crosslinking cellulose nanofibers-reinforced zwitterionic poly (ionic liquid) organohydrogel with high-stretchable, anti-freezing, anti-drying as strain sensor application - Dong Fu; Linhui Xing; Yang Xie; Peng Li; Fan Yang; Xin Sui; Jiaying Liu; Jialong Chi; Bo Huang; Jun Shen (Carbohydrate Polymers, 2025)

Dynamics of soil phosphorus fractions during the early recovery stage of two typical plantations in China after strip clearcutting - Linhui Zhang; Jihong Li; Su Chen; Wenlan Huang; Lulu Huang; Hongfeng Zhu; Yuanxiang Tang; Han Li; Chengming You; Lixia Wang; Sining Liu; Hongwei Xu; et al. (CATENA, 2025)

Ion-exchange induced multiple effects to promote uranium uptake from nonmarine water by micromotors - Linhui Fu; Kai Feng; Qianqian Li; Mengting Qin; Jing Yang; Xinle Zhang; Ling Chen; Jiang Gong; Jinping Qu; Ran Niu (Journal of Hazardous Materials, 2024)

A novel Zobellella endophytica W14 strain for nitrogen removal from hypersaline wastewater through simultaneous nitrification and denitrification - Nan Hu; Yingnan Li; Jiahui Yin; Zixuan Ren; Junyi Li; Jialin Zhao; Lixin Wang; Linhui Wu (Journal of Environmental Management, 2024)

A smartphone-based supramolecular biosensor for portable and rapid detection of buprofezin in real food samples - Yilin Zhan; Na Li; Tianyi Qin; Linhui Peng; Weihua Deng; Zhongyong Xu; Lei Wang; Immanuel David Charles; Bin Liu (Food Chemistry, 2024)

Unveiling cold Code: Acinetobacter calcoaceticus TY1′s adaptation strategies and applications in nitrogen treatment - Jiahui Yin; Junyi Li; Hongliang Xie; Yongman Wang; Jialin Zhao; Lixin Wang; Linhui Wu (Bioresource Technology, 2024)

6-Phosphogluconate dehydrogenase 2 bridges the OPP and shikimate pathways to enhance aromatic amino acid production in plants - Qian Tang; Yuxin Huang; Zhuanglin Shen; Linhui Sun; Yang Gu; Huiqing He; Yanhong Chen; Jiahai Zhou; Limin Zhang; Cuihuan Zhao; Shisong Ma; Yunhai Li; et al. (Science China Life Sciences, 2024)

Exploring the material basis and molecular targets of Changma Xifeng tablet in treating Tourette syndrome: an integrative approach of network pharmacology and miRNA analysis - Jing Peng; Qiaoling Li; Linhui Liu; Ping Gao; Lipeng Xing; Li Chen; Hui Liu; Zhisheng Liu (Metabolic Brain Disease, 2024)

Enhance the removal of pyrene by 3,4-ethylene dioxythiophene modified electrode in microbial electrochemical system - Xian Cao; Sirapat Khodseewong; Linhui Jiang; Yali Yuan; Shuai Zhang; Takashi Sakamaki; Xianning Li (Journal of Environmental Chemical Engineering, 2024)

Enhanced uranium extraction using a nanostructured photothermal hydrogel membrane - Zhipeng Liu; Kai Feng; Xinle Zhang; Linhui Fu; Jiaxin Ren; Rui Gao; Shihao Ding; Wenqian Xing; Yiwen Li; Jiaji Cheng; Qiang Li; Jiang Gong; et al. (Chemical Engineering Journal, 2024)

Downregulating DNA methyltransferase 3B by suppressing the PI3K/Akt signaling pathway enhances the chemosensitivity of glioblastoma to temozolomide - Wenwu Kan; Linhui Gao; Jingnan Chen; Li Chen; Guojun Zhang; Bilie Hao; Min He; Xudong Chen; Cheng Wang (Molecular Neurobiology, 2024)
Glioblastoma (GBM) is the most common malignant brain tumor and has the poorest prognosis attributed to its chemoresistance to temozolomide (TMZ), the first-line drug for treating GBM. TMZ resistance represents a significant obstacle to successful GBM treatment, necessitating the development of new strategies to overcome this resistance and augment the chemosensitivity of GBM cells to TMZ. This study established a TMZ-resistant U251 (U251-TMZ) cell line by exposing it to increasing doses of TMZ in vitro. We focused on the DNA methyltransferase 3B (DNMT3B) gene, phosphorylated Akt (p-Akt), total Akt (t-Akt), phosphorylated PI3K (p-PI3K), and total PI3K (t-PI3K) protein expression. Results showed that the DNMT3B gene was significantly upregulated in the U251-TMZ cell line. The p-Akt and p-PI3K protein expression in U251-TMZ cells was also significantly elevated. Moreover, we found that DNMT3B downregulation was correlated with the increased chemosensitivity of GBM cells to TMZ. LY294002 suppressed the PI3K/Akt signaling pathway, leading to a notable inhibition of PI3K phosphorylation and a significant decrease in DNMT3B expression in U251-TMZ cells. Given that DNMT3B expression is mediated by the PI3K/Akt signaling pathway, its downregulation further increased the chemosensitivity of GBM cells to TMZ and therefore is a promising therapeutic for GBM treatment. Our results suggested that DNMT3B downregulation can inhibit the proliferation of GBM cells and induce GBM cell apoptosis in vitro. In addition, the PI3K/Akt signaling pathway plays an important role in the chemosensitivity of GBM cells to TMZ by regulating DNMT3B expression.

Interaction and selective treatment of lead-zinc flotation wastewater for wastewater recycling using ectrocatalytic internal micro-electrolysis - Hongyan Ma; Chen Jiang; Xuan Zhu; Xin Zheng; Wenyi Zhou; Lirong Wang; Ming Zhao; Linhui Feng; Xiaojun Xu; Ciming Kong; Tianguo Li (Journal of Cleaner Production, 2024)

Cyanidin prevents cardiomyocyte apoptosis in mice after myocardial infarction - Deng Gang; Ouyang Qing; Yongzheng Yang; Muqaddas Masood; Yu-Hong Wang; Jiang Linhui; Su Haotao; Ge Li; Chi Liu; Moussa Ide Nasser; Ping Zhu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Assessing the performance of GNSS PPP-AR using OSB products from different analysis centers - Qi Zhang; Shuhui Li; Lihua Li; Linhui Zhao; Zihang Niu; Huimin Cao (Earth Science Informatics, 2024)

Impact of Climate Change on Water Diversion Risk of Inter‑Basin Water Diversion Project - Linhui Mu; Tao Bai; Dong Liu; Lei Li (Water Resources Management, 2024)

Regulation of nitrite-dependent anaerobic methane oxidation bacteria by available phosphorus and microbial communities in lake sediments of cold and arid regions - Zixuan Ren; Yingnan Li; Jiahui Yin; Ziwen Zhao; Nan Hu; Manping Zhao; Yongman Wang; Lixin Wang; Linhui Wu (Science of The Total Environment, 2024)

Time-sequenced hydrodynamics prediction system for underwater vehicles based on AI edge computing - Yuqing Hou; Fei Duan; Wenkang Zhu; Hui Li; Shengnan Shen; Xinhui Shen; Jiayue Wang; Yicang Huang; Wei Wei; Xin Liu; Linhui Liu (Ocean Engineering, 2024)

New dating indicates intermittent human occupation of the Nwya Devu Paleolithic site on the high-altitude central Tibetan Plateau during the past 45,000 years - Junyi Ge; Xiaoling Zhang; Shejiang Wang; Linhui Li; Wei He; Yingshuai Jin; Peiqi Zhang; Bing Xu; Chenglong Deng; John W. Olsen; Zhengtang Guo; Xing Gao (Science China Earth Sciences, 2024)

Comparative analysis of codon usage patterns in the chloroplast genomes of nine forage legumes - Mingkun Xiao; Xiang Hu; Yaqi Li; Qian Liu; Shaobin Shen; Tailing Jiang; Linhui Zhang; Yingchun Zhou; Yuexian Li; Xin Luo; Lina Bai; Wei Yan (Physiology and Molecular Biology of Plants, 2024)
Leguminosae is one of the three largest families of angiosperms after Compositae and Orchidaceae . It is widely distributed and grows in a variety of environments, including plains, mountains, deserts, forests, grasslands, and even waters where almost all legumes can be found. It is one of the most important sources of starch, protein and oil in the food of mankind and also an important source of high-quality forage material for animals, which has important economic significance. In our study, the codon usage patterns and variation sources of the chloroplast genome of nine important forage legumes were systematically analyzed. Meanwhile, we also constructed a phylogenetic tree based on the whole chloroplast genomes and protein coding sequences of these nine forage legumes. Our results showed that the chloroplast genomes of nine forage legumes end with A/T bases, and seven identical high-frequency (HF) codons were detected among the nine forage legumes. ENC-GC3s mapping, PR2 analysis, and neutral analysis showed that the codon bias of nine forage legumes was influenced by many factors, among which natural selection was the main influencing factor. The codon usage frequency showed that the Nicotiana tabacum and Saccharomyces cerevisiae can be considered as receptors for the exogenous expression of chloroplast genes of these nine forage legumes. The phylogenetic relationships of the chloroplast genomes and protein coding genes were highly similar, and the nine forage legumes were divided into three major clades. Among the clades Melilotus officinalis was more closely related to Medicago sativa , and Galega officinalis was more closely related to Galega orientalis . This study provides a scientific basis for the molecular markers research, species identification and phylogenetic studies of forage legumes.

KLF4 facilitates chromatin accessibility remodeling in porcine early embryos - Wei Zhu; Guowei Bu; Ruifeng Hu; Jixiang Zhang; Lianyong Qiao; Kai Zhou; Tingting Wang; Qiao Li; Jingjing Zhang; Linhui Wu; Yali Xie; Taotao Hu; et al. (Science China Life Sciences, 2024)

Response of soil phosphorus fractions to litter removal in subalpine coniferous forest - Linhui Zhang; Ya Shen; Yifan Hu; Jihong Li; Yao Liu; Su Chen; Lixia Wang; Sining Liu; Han Li; Chengming You; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2023)

Coupling of soil methane emissions at different depths under typical coastal wetland vegetation types - Kun Li; Zihao Wang; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xiaoyan Shen; Xiaoya Xu; Qingfeng Chen (Chemosphere, 2023)

Observation of nitrogen oxide-influenced chlorine chemistry and source analysis of Cl2 in the Yangtze River Delta, China - Fangbing Li; Dan Dan Huang; Wei Nie; Yee Jun Tham; Shengrong Lou; Yuanyuan Li; Linhui Tian; Yuliang Liu; Min Zhou; Haichao Wang; Liping Qiao; Hongli Wang; et al. (Atmospheric Environment, 2023)

Direct conversion of CH4 and CO2 to alcohols using plasma catalysis over Cu/Al(OH)3 catalysts - Li Wang; Yuezhao Wang; Linhui Fan; Hongli Xu; Bowen Liu; Jiaren Zhang; Yimin Zhu; Xin Tu (Chemical Engineering Journal, 2023)

Soil nitrogen content and key functional microorganisms influence the response of wetland anaerobic oxidation of methane to trivalent iron input - Zihao Wang; Kun Li; Feifei Yan; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xinyi Xu; Ying Zhang; Xiaoyan Shen; et al. (Chemosphere, 2023)

Soil nitrogen substances and denitrifying communities regulate the anaerobic oxidation of methane in wetlands of Yellow River Delta, China - Zihao Wang; Kun Li; Xiaoyan Shen; Feifei Yan; Xinkun Zhao; Yu Xin; Linhui Ji; Qingyue Xiang; Xinyi Xu; Daijia Li; Junhao Ran; Xiaoya Xu; et al. (Science of The Total Environment, 2023)

CACNA1C-AS2 inhibits cell proliferation and suppresses cell migration and invasion via targeting FBXO45 and PI3K/AKT/mTOR pathways in glioma - Tong Cao; Yue Cui; Yingying Wang; Linhui Wu; Ke Yu; Kai Chen; Jun Xia; Yuyun Li; Zhiwei Peter Wang; Jia Ma (Apoptosis, 2022)

Suppressed Thermocline Mixing in the Center of Anticyclonic Eddy in the North South China Sea - Yongfeng Qi; Huabin Mao; Xia Wang; Linhui Yu; Shumin Lian; Xianpeng Li; Xiaodong Shang (Journal of Marine Science and Engineering, 2021)
Direct microstructure observations and fine-scale measurements of an anticyclonic mesoscale eddy were conducted in the northern South China Sea in July 2020. An important finding was that suppressed turbulent mixing in the thermocline existed at the center of the eddy, with an averaged diapycnal diffusivity at least threefold smaller than the peripheral diffusivity. Despite the strong background shear and significant wave–mean flow interactions, the results indicated that the lack of internal wave energy in the corresponding neap tide period during measurement of the eddy’s center was the main reason for the suppressed turbulent mixing in the thermocline. The applicability of the fine-scale parameterization method in the presence of significant wave–mean flow interactions in a mesoscale eddy was evaluated. Overprediction via fine-scale parameterization occurred in the center of the eddy, where the internal waves were inactive; however, the parameterization results were consistent with microstructure observations along the eddy’s periphery, where active internal waves existed. This indicates that the strong background shear and wave–mean flow interactions affected by the mesoscale eddy were not the main contributing factors that affected the applicability of fine-scale parameterization in the northern South China Sea. Instead, our results showed that the activity of internal waves is the most important consideration.

The construction of high precision geostrophic currents based on new gravity models of GOCE and satellite altimetry data - Wenyan Sui; Junru Guo; Jun Song; Zhiliang Liu; Meng Wang; Xibin Li; Yanzhao Fu; Yongquan Li; Yu Cai; Linhui Wang; Lingli Li; Xiaofang Guo; et al. (Acta Oceanologica Sinica, 2021)

Combined addition of chemical and organic amendments enhances plant resistance to aboveground herbivores through increasing microbial abundance and diversity - Linhui Jiang; Michael Bonkowski; Ling Luo; Paul Kardol; Yu Zhang; Xiaoyun Chen; Daming Li; Zhenggao Xiao; Feng Hu; Manqiang Liu (Biology and Fertility of Soils, 2020)

Unexpected rise of ozone in urban and rural areas, and sulfur dioxide in rural areas during the coronavirus city lockdown in Hangzhou, China: implications for air quality - Liqiang Wang; Mengying Li; Shaocai Yu; Xue Chen; Zhen Li; Yibo Zhang; Linhui Jiang; Yan Xia; Jiali Li; Weiping Liu; Pengfei Li; Eric Lichtfouse; et al. (Environmental Chemistry Letters, 2020)

Complete genome analysis of a Staphylococcus aureus phage (vBSM-A1) - Huijun Geng; Meixia Zhang; Xiaoyu Li; Lili Wang; Cong Cong; Huijing Cui; Linhui Wang; Yongping Xu (Archives of Microbiology, 2020)

Organic Matter Pollution During the Spring Thaw in Hulun Lake Basin: Contribution of Multiform Human Activities - Wenlin Wang; Wenjing Li; Yan Yan; Bo Liu; Tanjing Wang; Sichen Mao; Linhui Song; Huashan Dou; Wen Ao; Changxin Zou (Bulletin of Environmental Contamination and Toxicology, 2020)

Spatiotemporal variability of phytoplankton functional groups in a shallow eutrophic lake from cold, arid regions - Ye Jin; Ruihong Yu; Zhuangzhuang Zhang; Qi Zhang; Meixia Li; Zhengxu Cao; Linhui Wu; Yanling Hao (Environmental Monitoring and Assessment, 2020)

Danshen formula granule and salvianic acid A alleviate ethanol-induced neurotoxicity - Yujia Li; Hui Chen; Yating Yang; Menglan Niu; Jiaxin Wang; Yuanyuan Wu; Linhui Niu; Hongliang Liu; Dengke Bao (Journal of Natural Medicines, 2020)

Gibberellin stimulates regrowth after defoliation of sheepgrass (Leymus chinensis) by regulating expression of fructan-related genes - Yueyue Cai; Linhui Shao; Xiuqing Li; Gongshe Liu; Shuangyan Chen (Journal of Plant Research, 2016)

The Adsorption and Desorption of Pb2+ and Cd2+ in Freeze–Thaw Treated Soils - Linhui Li; Jincai Ma; Meng Xu; Xu Li; Jiahui Tao; Guanzhu Wang; Jitong Yu; Ping Guo (Bulletin of Environmental Contamination and Toxicology, 2016)

Rapid development of proteomics in China: from the perspective of the Human Liver Proteome Project and technology development - Ning Li; ZhongWei Xu; LinHui Zhai; YanChang Li; FengXu Fan; JunJie Zheng; Ping Xu; FuChu He (Science China Life Sciences, 2014)

Selection of surfactant in remediation of DDT-contaminated soil by comparison of surfactant effectiveness - Ping Guo; Weiwei Chen; Yueming Li; Tao Chen; Linhui Li; Guanzhu Wang (Environmental Science and Pollution Research, 2014)

Dishevelled-2 silencing reduces androgen-dependent prostate tumor cell proliferation and migration and expression of Wnt-3a and matrix metalloproteinases - Yinhui Yang; Li Jiao; Jianguo Hou; Chuanliang Xu; Linhui Wang; Yongwei Yu; Yun Li; Chun Yang; Xia Wang; Yinghao Sun (Molecular Biology Reports, 2013)